2013
DOI: 10.1111/cen.12350
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic factors associated with pediatric diabetic ketoacidosis admissions in Southern West Virginia

Abstract: This study identifies socioeconomic factors associated with children admitted for DKA in WV. Patients at higher risk for DKA include those with elevated HbA1c, African American race and those covered by Medicaid/CHIPS (thereby presumed lower socioeconomic status). Findings can be utilized to identify patients at highest risk for DKA and implementation of prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 14 publications
3
14
0
Order By: Relevance
“…Our study was able to give some insight into the characteristics of Australian children with at least two admissions for DKA. Consistent with previous studies, we found residence in regional and rural locations and in areas of socioeconomic disadvantage to be associated with repeated DKA‐related hospitalizations. This may reflect reduced access to health care, insulin therapy, or glucose testing equipment.…”
Section: Discussionsupporting
confidence: 92%
“…Our study was able to give some insight into the characteristics of Australian children with at least two admissions for DKA. Consistent with previous studies, we found residence in regional and rural locations and in areas of socioeconomic disadvantage to be associated with repeated DKA‐related hospitalizations. This may reflect reduced access to health care, insulin therapy, or glucose testing equipment.…”
Section: Discussionsupporting
confidence: 92%
“…non‐private insurance or no insurance) compared with ‘higher’ insurance status (e.g. private insurance or commercial insurance) and the occurrence of diabetic ketoacidosis . By contrast, a German study found that public compared with private health insurance status did not significantly increase the risk of experiencing acute diabetic ketoacidosis .…”
Section: Resultsmentioning
confidence: 91%
“…Associations between individual‐level and area‐level educational attainment, individual‐level family/household income, insurance status and socio‐economic status, as well as area‐level deprivation and the occurrence of diabetic ketoacidosis were considered in eight studies (Tables , , and ) . Four studies were performed in youths and four in adults .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, low socioeconomic status and low parental education have been found associated with increased risk of DKA4344. Type 1 diabetes is a major risk factor for diabetic ketoacidosis across the world and is prevalent in Kuwaiti children45.…”
Section: Discussionmentioning
confidence: 99%